2021
DOI: 10.1371/journal.pone.0247023
|View full text |Cite
|
Sign up to set email alerts
|

The association between body mass index and severity of Coronavirus Disease 2019 (COVID-19): A cohort study

Abstract: Objectives The coronavirus disease 2019 (COVID-19) has become a worst pandemic. The clinical characteristics vary from asymptomatic to fatal. This study aims to examine the association between body mass index (BMI) levels and the severity of COVID-19. Methods and study design A cohort study included 147 adult patients with confirmed COVID-19 were categorized into 4 groups by BMI levels on admission: <18.5 (underweight), 18.5–22.9 (normal weight), 23.0–24.9 (overweight), and ≥25.0 kg/m2 (obese). Rates of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 23 publications
(15 reference statements)
6
24
2
Order By: Relevance
“…Meanwhile, underweight COVID-19 patients are at risk of developing acute kidney injury, which could worsen the patient's condition. 40 In this study, laboratory parameters were not significantly different within various BMI groups. This might also be influenced by other conditions of the patients.…”
Section: Discussionmentioning
confidence: 43%
“…Meanwhile, underweight COVID-19 patients are at risk of developing acute kidney injury, which could worsen the patient's condition. 40 In this study, laboratory parameters were not significantly different within various BMI groups. This might also be influenced by other conditions of the patients.…”
Section: Discussionmentioning
confidence: 43%
“…There are still no visible and definitive ways to defeat the disease. Many studies showed that a high BMI is a cause of a lot of complications during COVID-19 [9] , [11] , [16] , [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, these countries have a good system for data gathering and data sharing. Nevertheless, the economically prosperous countries differ in other specific features, for instance, these countries have a lot of people with NCD, and BMI more than 25 kg per meter square [8] , [9] , [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also shown that obesity is a risk factor for ICU admission [ 19 , 21 , 22 , 24 , 28 , 32 , 33 ]. A meta-analysis published early in the COVID-19 pandemic found that obesity was associated with a 39% increased risk of developing critical illness, which included ICU admission [ 34 ].…”
Section: Hospitalization and Icu Admissionmentioning
confidence: 99%